Naevus lipomatosus cutaneous superficialis in a young boy - Gruffydd Perks; Iman Kotb; Dawn Fleming; Ross Hearn (Skin Health and Disease, 2026)
A 12-year-old boy presented with a slowly enlarging, papillomatous plaque on the sacral area and natal cleft that was present since infancy. The clinical appearance suggested a broad differential diagnosis. Histopathology demonstrated a polypoid lesion covered by squamous epithelium. Mature adipose tissue was present within the dermis, extending into the papillary dermis but not connected to the fat of the underlying subcutis.